2014
DOI: 10.1007/s00253-014-5779-3
|View full text |Cite
|
Sign up to set email alerts
|

Succinic acid-producing biofilms of Actinobacillus succinogenes: reproducibility, stability and productivity

Abstract: Continuous anaerobic fermentations were performed in a biofilm reactor packed with Poraver® beads. Dilution rates (D) varied between 0.054 h -1 and 0.72 h -1 and D-glucose and CO 2 gas were used as carbon substrates. Steady-state conditions were shown to be repeatable and independent of the operational history. Production stability was achieved over periods exceeding 80 h at values of D below 0.32 h -1 . In these situations, steady-state variation (expressed as fluctuations in NaOH neutralisation flow rates) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 27 publications
2
24
1
Order By: Relevance
“…Similar to previous continuous, biofilm studies on A. succinogenes Bradfield and Nicol, 2016;Brink and Nicol, 2014;Maharaj et al, 2014), in the current study, the succinic acid yield on substrate ( Figure 2A) and the ratio of succinic acid to acetic acid (Y AASA ; Figure 2B) increased with increasing succinic acid titre (C SA ). Furthermore, the formic acid-to-acetic acid ratio (Y AAFA ) decreased with increasing C SA ( Figure 2B), indicating increased pyruvate-or formate dehydrogenase activity It has been suggested that these trends are linked to a titre-dependent shift in metabolism from a growth to a non-growth or stationary mode Brink and Nicol, 2014), with associated incomplete closures of mass and redox balances.…”
Section: Continuous Glucose and Xylose Fermentationssupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to previous continuous, biofilm studies on A. succinogenes Bradfield and Nicol, 2016;Brink and Nicol, 2014;Maharaj et al, 2014), in the current study, the succinic acid yield on substrate ( Figure 2A) and the ratio of succinic acid to acetic acid (Y AASA ; Figure 2B) increased with increasing succinic acid titre (C SA ). Furthermore, the formic acid-to-acetic acid ratio (Y AAFA ) decreased with increasing C SA ( Figure 2B), indicating increased pyruvate-or formate dehydrogenase activity It has been suggested that these trends are linked to a titre-dependent shift in metabolism from a growth to a non-growth or stationary mode Brink and Nicol, 2014), with associated incomplete closures of mass and redox balances.…”
Section: Continuous Glucose and Xylose Fermentationssupporting
confidence: 89%
“…As a result, less biofilm was present in the fermenter compared to previous fermentations using a similar fermentation setup Bradfield and Nicol, 2016;Maharaj et al, 2014).…”
Section: Continuous Fermentationsmentioning
confidence: 98%
See 1 more Smart Citation
“…succinogenes [11,12]. However, the dehydrogenase activity appears to be lower in the case of xylose since YAAFA does not decrease to the same extent as in the glucose study.…”
Section: Figmentioning
confidence: 86%
“…Various microbial platforms have been explored for bio-production of SA with the best bench-scale performance achieved by Actinobacillus succinogenes [11][12][13][14], Anaerobiospirillum succiniciproducens [15,16], Mannheimia succiniciproducens [17][18][19], and engineered strains of Escherichia coli [20][21][22].…”
Section: Introductionmentioning
confidence: 99%